2012
DOI: 10.1242/jeb.062703
|View full text |Cite
|
Sign up to set email alerts
|

The effects of asymmetric length trajectories on the initial mechanical efficiency of mouse soleus muscles

Abstract: SUMMARYAsymmetric cycles with more than half of the cycle spent shortening enhance the mechanical power output of muscle during flight and vocalisation. However, strategies that enhance muscle mechanical power output often compromise efficiency. In order to establish whether a trade-off necessarily exists between power and efficiency, we investigated the effects of asymmetric muscle length trajectories on the maximal mechanical cycle-average power output and initial mechanical efficiency (E i ). Work and heat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…The use of regional heat measurements to estimate whole muscle energy consumption (e.g. Hill, 1949;Woledge et al, 1985;Barclay et al, 1993;Barclay and Weber, 2004;Holt and Askew, 2012) is dependent on the assumption of uniform heat production throughout the muscle. It has been hypothesized that non-uniform heat production could occur because of non-uniformity in sarcomere strain arising during active stretch and/or relaxation (Hill, 1949;Linari et al, 2003;Woledge et al, 1985) and uneven distribution of strain across entire muscles (Hill, 1949;Ahn et al, 2003;Carr et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of regional heat measurements to estimate whole muscle energy consumption (e.g. Hill, 1949;Woledge et al, 1985;Barclay et al, 1993;Barclay and Weber, 2004;Holt and Askew, 2012) is dependent on the assumption of uniform heat production throughout the muscle. It has been hypothesized that non-uniform heat production could occur because of non-uniformity in sarcomere strain arising during active stretch and/or relaxation (Hill, 1949;Linari et al, 2003;Woledge et al, 1985) and uneven distribution of strain across entire muscles (Hill, 1949;Ahn et al, 2003;Carr et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…These procedures have been reported in greater detail previously (Holt and Askew, 2012). Briefly, muscles were suspended in a Perspex flow-through muscle chamber circulated with oxygenated Ringer's solution at 20°C.…”
Section: Isometric and Force-velocity Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…An isometric tetanus was performed to determine peak isometric force (F 0 ) (Holt and Azizi, 2014). After-loaded isotonic tetanic contractions (Askew and Marsh, 1997;Holt and Askew, 2012) (Fig. 2) were performed at a range of forces (0.1 to 0.9 F 0 ) to determine the relationships between force and muscle velocity, force and fiber velocity, and force and gear ratio (muscle velocity/ fiber velocity) (Azizi et al, 2008).…”
Section: Contractile Tissue Properties and Gear Ratiosmentioning
confidence: 99%
“…Asymmetric saw-tooth strain patterns have been shown to be an efficient mechanism for increasing muscle power output (Askew and Marsh, 1997;Holt and Askew, 2012), and the possibility exists for animals to adjust the symmetry of muscle length trajectories in order to modulate power. Interestingly, we found that during the first and final wingbeats of short flights, the pectoralis strain pattern was more symmetrical -not less so -despite the expectation that these wingbeats would have the greatest power requirements.…”
Section: Muscle Strain and Activation Patternsmentioning
confidence: 99%